Relationship between NT-proBNP and the ejection fraction during intensive care variety in polytrauma patients with concomitant cardiac disorder - Lutska, Svitlana; Volkova, Yulia; Mykhnevych, Kostiantyn (Journal of Education, Health and Sport, 2021)
The aim. To research the impact of chronic heart failure within different origin in case of polytrauma without myocardial injury. Materials and methods. The study the analyzed results of intensive care in 95 patients with polytrauma between the ages of 25 and 83. All patients were divided into 3 groups. Group C included 29 patients without chronic heart failure (CHF), groups C - 33 patients with CHF, the presence which was confirmed by the level of NT-proBNP more than 100 pg/ml, group E - 33 patients with CHF. Patients of groups K and C received standard intensive care, patients of group E additionally received ethylmethylhydroxypyridine succinate (EMGPS). The study was carried out at three stages: during admission to the hospital, at the 3rd and 7th day. During admission, the level of Th I was determined in order to exclude traumatic or other acute myocardial lesions. At a concentration of Tn I more than 0.3 ng/ml, patients were not included in the study. Results. During admission, NT-proBNP level in all K-group patients did not exceed 87 pg/ml throughout the study. The ejection fraction (EF) was averaged 53,7±3,4%. The NT-proBNP dynamics were as followed by 116.4±7.0, 114.4±7.4, 109.1±8.5 pg/ml. The NT-proBNP and EF correlation coefficient was according to the stages -0.84±0.06, -0.74±0.08, -0.68±0.09. The value of the EF at hospitalization in group C was 47.9±4.7%, on the 3rd day 52.2±5.2% (p < 0.001), and by 7th - until 56.8±6.9% (p < 0.001). NT-proBNP level in E patients: 119.2±10.8, 113.2±8.1 (p= 0.02), 65.2±23.3 (p < 0.0001). At stage 1 and 2, a strong negative correlation effect was observed (-0.78±0.07 and -0.77±0.07, accordingly), at the 3 stage the communication disappeared (0.07±0.17). Within admission EF level was 47.5±6.9 %. Conclusions. The level of NT-proBNP authentically reflects the relationship with chronic heart failure. There is also a strong correlation between NT-proBNP and EF. Therefore, it is clear from the study that NT-proBNP has not undergone changes in group K (87 pg/ml), in contrast to patients of groups C (116.4±7.0,114.4±7.4, 109.1±8.5 pg/ml) and E (119.2±10.8, 113.2±8.1 (p =0.02), 65.2±23.3 (p < 0.0001) who had concomitant disorder such as chronic heart failure.